Upaya Meningkatkan Keaktifan Belajar Peserta Didik Melalui Model Discovery Learning Berbantuan Media Pembelajaran - S, Agavin M; Sofwan, M.; Iskandar, Dedi; Wahyuni, Ida (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2024)
In the learning process, the active learning of students is important to create meaningful and learner-centered learning by activities. Active students will find it easier to understand learning material because they experience learning directly so that they can achieve optimal learning outcomes. The purpose of this study was to determine the extent to which the increase in student learning activeness through the implementation of the discovery learning model assisted by instructional media in Pancasila education subjects in class IV SDN 19 Jambi City. The research method used is Classroom Action Research (PTK) which is carried out in 2 cycles. In this study, researchers used observation sheets as research instruments. The observation sheet used consists of several assessment indicators that can measure the learning activeness of students. The results showed that the discovery learning model assisted by instructional media could increase the learning activeness of students, in cycle 1 there was a frequency of 12 active students with a percentage of 57.24%. Then in cycle 2 the frequency increased to 17 students with a percentage reaching 81.09%. So it can be seen that the frequency of students increased from 12 to 17 students. Based on the observation results, it can also be seen that students have high enthusiasm to be actively involved in learning activities. So it can be concluded that the discovery learning model with the help of learning media can increase the learning activeness of students.